ANALISIS HUKUM EKONOMI SYARIAH TERHADAP PERATURAN MENTERI PUPR NO. 16/PRT/M/2017 TAHUN 2017 TENTANG TRANSAKSI TOL NONTUNAI DI JALAN TOL - Jelisa Awaliyah Humaedi; Sofian Al-Hakim (Al-Muamalat: Jurnal Ekonomi Syariah, 2018)
PUPR Ministerial Regulation No.16 / PRT / M / 2017 concerning Non-cash Toll Transactions on Toll Roads. Electronic Toll (E-Toll) is a program in the form of an electronic toll payment service in the form of an electronic card used to make payments for entering toll roads. The use of e-toll is only by using a card that is pasted and finished within 4 seconds. The e-toll card is issued by PT. Jasa Marga. The technology used by E-Toll cards is RFID (Radio Frequency Identification) where transactions can be done remotely (contactless). Toll cards do not need a PIN or signature. E-toll is made because of the congestion that always occurs at the toll gate with the aim of shortening the toll payment time so that there is no longer a long queue. The research framework in this study is to analyze the phenomenon of the emergence of PUPR Ministerial Regulation No.16 / PRT / M / 2017 concerning Transaction of Non-toll Toll Roads, which is linked to Law No.7 of 2011 concerning Currency in relation to the Al-Hurriyyah Principle. The writing method used is the empirical juridical method. That is research on legal identification (unwritten law) based on the laws that apply in society, namely customary law and Islamic law. In this study, researchers must deal with citizens who are the object of research so that many regulations are not written in the community. The results of this study indicate that (1) The birth of PUPR Ministerial Regulation No.16 / PRT / M / 2017 concerning Transaction of Non-cash Toll Roads, is an effort to realize a transparent, participatory government and also to develop electronic-based governance in the framework of improve the quality of public services effectively and efficiently. (2) Non-cash transactions on the toll road, provide more benefits than mafsadat. So basically the government program has provided a way out of traffic congestion problems, although at the same time it reduces user freedom.